The SAGA histone deubiquitinase module controls yeast replicative lifespan via Sir2 interaction - McCormick, Mark A. (Cell Rep, 2014)
We have analyzed the yeast replicative lifespan of a large number of ORF deletions. Here we report that strains lacking genes SGF73, SGF11, and UBP8, encoding SAGA/SLIK complex histone deubiquitinase module (DUBm) components, are exceptionally long-lived. Strains lacking other SAGA/SALSA components, including the acetyltransferase encoded by GCN5, are not long-lived; however, these genes are required for the lifespan extension observed in DUBm deletions. Moreover, the SIR2-encoded histone deacetylase is required, and we document both a genetic and physical interaction between DUBm and Sir2. A series of studies, assessing Sir2-dependent functions, lead us to propose that DUBm strains are exceptionally long-lived because they promote multiple pro-longevity events, including reduced rDNA recombination and altered silencing of telomere-proximal genes. As ataxin-7, the human Sgf73 ortholog, causes the neurodegenerative disease spinocerebellar ataxia type 7, our findings indicate that the genetic and epigenetic interactions between DUBm and SIR2 will be relevant to neurodegeneration and aging.